Differences On Students’ Learning Outcomes With High And Low Achievement Motivation - Sriati Usman; Mochtar Marhum; Aminah Suriaman; Amir Pattu (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2021)
This research aims to examine the difference of students’ learning outcomes as an effect of achievement motivation in writing an English Essay through film-assisted inquiry-based learning method. It was a quasi-experimental research non-equivalent control group design which implemented into two different parallel classes. They are experimental group and control group, in which seventy two students were accepted as subject surveyed through cluster random sampling technique. Data of students’ learning outcomes collected through pre-test and post-test. While data of students’ achievement motivation level collected through questionnaire. The data of pre-test was taken before treatment, used to determine students’ variance, whereas post-test data was taken after treatment entirely finished to examine students’ learning outcomes differences. Data analysis using SPSS 22 with ANOVA Factorial 2x2 (two- way ANOVA. The hypothesis testing was conducted in 5% of significance level. The result of data analysis indicates that the p-value of t-counted is 0.000 lower than 0.05(˂0.05). It can be interpreted that there is a significant difference of learning outcomes between the students who have a high achievement motivation and those who have low one in writing an English essay through film-assisted inquiry-based learning method. Moreover, the students with high achievement motivation have better achievement than the students with low achievement motivation.